Explanation:
As given, AB = AD, so that triangle ABD is an isosceles triangle.
=> In triangle ABD: m∠ABD = m∠ADB
As we can see:
+) The measure of supplementary angle of Angle ADC is 65°.
=> m∠ADC = 180° - 65° = 115°.
+) The measure of vertical angle of Angle BCD is 20°.
=> m∠BCD = 20°.
+) m∠BAD = 110°
As ABCD is a quadrilateral, so that total measure of its 4 interior angles are 360°:
⇒ m∠ADC + m∠BCD + m∠CBA + m∠BAD = 360°
⇔ 115° + 20° + m∠CBA + 110° = 360°
⇔ m∠CBA = 360° - 110° - 20° - 115° = 115°
⇒ m∠CBA = m∠ADC = 115°
We have:
+) m∠CBA = m∠CBD + m∠ABD
+) m∠ADC = m∠CDB + m∠ADB
As m∠CBA = m∠ADC; m∠ABD = m∠ADB so that: m∠CBD = m∠CDB
In triangle BDC, m∠CBD = m∠CDB
=> BDC is an isosceles triangle.
=> CD = CB
In quadrilateral, CD = CB; AB = AD
=> there are two disjoint pairs of consecutive sides of a quadrilateral are congruent
=> ABCD is a kite (reverse of the kite definition)